Features of water metabolism of introduced varieties sea-вuckthorn (Experimental biology, 2015)
The article presents the results of research on water regime of new varieties sea buckthorn in the climatic conditions of the Chui valley of Kyrgyzstan as well as is given a distinguishing characteristic of new varieties compared to the local forms of sea-buckthorn berries. The most perspective by the state of water regime and the adverse ecological conditions of the variety. However, the average rank close location to each other talk about common positive attributes of all plants according studied traits. The loss of water by plants occurs due ecological and climatic conditions region of investigations, but also depends on the morphology and anatomical structure of leaves. The revealed a direct relationship between by transpiration and water absorption not typical for the entire series and are a controversial subject in positive and negative is the only case in the mass.
Keywords: sea buckthorn; introduction; water regime; transpiration rate; water content; water losses; water absorption